Endogenous De Novo Synthesis of Isopropanol Following Severe Non-Diabetic Ketoacidosis in a Patient With Duchenne Muscular Dystrophy - Bihlmaier, Karl; Grampp, Steffen; Willam, Carsten; Schiffer, Mario; Herbst, Larissa (Journal of Endocrinology and Metabolism, 2022)
In Duchenne muscular dystrophy (DMD), patients seem prone to severe metabolic acidosis following excessive bicarbonate loss due to laxative use or gastrointestinal disorders. In addition, hypoalimentation and fasting can cause life-threatening non-diabetic ketoacidoses with acetonemia in these patients. Isopropanolemia instead is predominantly found following intoxication. Only few reports exist describing isopropanolemia in diabetic or alcoholic ketoacidosis. Here, we report on a patient suffering from DMD who developed lifethreatening non-diabetic ketoacidosis, acetonemia, and endogenous de novo synthesis of isopropanol following glucose fasting. We hypothesize isopropanolemia being a byproduct of acetone metabolism, possibly in association with a metabolic predisposition in patients with DMD such as an altered NADH/NAD(+) ratio leading to a reduction from acetone to isopropyl alcohol whilst in severe ketoacidosis.
CRIS-Team WoS Importer:2022-07-01
Keywords: Isopropanolemia; Acetonemia; Ketoacidosis; Refeeding syndrome; Duchenne muscular dystrophy